Menelisik praktik perhambaan di kampung Raja Prailiu, Sumba Timur: Sebuah kajian poskolonial dalam upaya memutus rantai perhambaan di era modern - Setyawan, Yusak Budi; Lena, Iston Umbu Kura (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
In this modern era, the practice of slavery in various forms can be found in multiple places in the world, including in Raja Prailiu Village, Sumba Timur, Nusa Tenggara Timur, Indonesia. This practice has been carried out by the Maramba (nobles) against the Ata (servants). This causes injustice and discrimination for the Ata people, who even experience violence, both physical and psychological. This research aims to study why this practice continues to be maintained and perpetuated, as well as propose efforts to break the chain of this kind of slavery so as not to cause further social problems, especially for the Ata. This research uses qualitative methods with a postcolonial approach. Data collection techniques included observation, in-depth interviews, and documentation. This research concerns efforts to eliminate various forms of slavery practices in society, especially in Raja Prailiu Village. This research found that this practice continues to occur because, as subalterns, the Ata’s voices are not heard, their experiences are silenced, and there is no